O PROEJA como espaço de formação docente - Barbosa, Maria Núbia (2014)
This study investigates teachers at the Federal Institute of Education, Science and Technology of Ceará – IFCE, Fortaleza Campus and how they become teachers of the National Program for the Integration of Vocational Education with Basic Education in the modality Youth and Adults Education – PROEJA in the institutional routine, considering their teaching practice in the classroom. The general objective is to understand how teachers are trained to teach in the Refrigeration and Air Conditioning Program – PROEJA at the IFCE, Fortaleza Campus, showing their perception of the syllabus and their experiences in the classroom. The specific objectives are to contextualize the institutional space of IFCE, as a way of understanding the phenomenon studied; to conceive syllabus and teacher training as the epistemological depth required for the analysis of empirical evidences; and to compare the prescriptive teacher training process to the experienced one, from the observations made in the classrooms and the interviews conducted with the subjects in the research. Based upon methodological theoretical references by Nóvoa (1992); Silva (2002a, 2002b); Giroux (1999); Pimenta and Anasrasiou (2002); Macedo (2011); Tardif (2002); Sacristan (2002) among others, the training of PROEJA vocational education teachers was investigated, revisiting the studies conducted by Manfredi (2002); Romanelli (2003); Queluz (2002); Ibernon (2004). The research used an interpretative descriptive and qualitative approach, developed based on contributions of the following authors: André (1995); Bodgan and Biklen (1994); Gil (1994); André e Lüdke (1986); Minayo (1994); Moreira and Caleffe (2006) and others. Their methodological content helped us to understand the representation on the training processes of the research participating subjects and their performances in the classroom. Regarding the recording of the collected data, the “board diary” technique was used for posterior analysis of the empirical evidence collected, and also through students’ and teachers’ speeches during the interviews. The subjects’ speech analysis generated the following categories: teacher training, EJA (Youth and Adult Education) and syllabus, which have been confronted with the methodological theoretical reference developed in the research. Concerning the results achieved, we highlight the discovery of creative ways by teachers in their practice with the PROEJA, as an attempt to overcome the absence of an institutional training to work with students of different backgrounds, trajectories and diverse identities in the development of their teaching practice.